2022
DOI: 10.1073/pnas.2110105119
|View full text |Cite
|
Sign up to set email alerts
|

SARS-CoV-2 prefusion spike protein stabilized by six rather than two prolines is more potent for inducing antibodies that neutralize viral variants of concern

Abstract: The spike (S) protein of severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) is the main target for neutralizing antibodies (NAbs). The S protein trimer is anchored in the virion membrane in its prefusion (preS) but metastable form. The preS protein has been stabilized by introducing two or six proline substitutions, to generate stabilized, soluble 2P or HexaPro (6P) preS proteins. Currently, it is not known which form is the most immunogenic. Here, we generated recombinant vesicular stomatitis virus … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
34
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
4
1

Relationship

1
8

Authors

Journals

citations
Cited by 45 publications
(48 citation statements)
references
References 45 publications
4
34
0
Order By: Relevance
“…The finding that a spike protein with six stabilizing proline substitutions resulted in higher neutralizing antibody titers than the version with two prolines is notable as revised structure-based designs of fusion glycoproteins do not always result in better immunogenicity despite improved protein expression and stability 95 . Our observation on the superior immunogenicity of the HexaPro construct adds to a recent publication by Zhang et al 96 during the preparation of this manuscript. On the contrary, a mRNA COVID-19 vaccine candidate based on the Hexapro variant and developed by Sanofi Pasteur failed to elicit nAbs in mice and non-human primates 97 .…”
Section: Discussionsupporting
confidence: 74%
“…The finding that a spike protein with six stabilizing proline substitutions resulted in higher neutralizing antibody titers than the version with two prolines is notable as revised structure-based designs of fusion glycoproteins do not always result in better immunogenicity despite improved protein expression and stability 95 . Our observation on the superior immunogenicity of the HexaPro construct adds to a recent publication by Zhang et al 96 during the preparation of this manuscript. On the contrary, a mRNA COVID-19 vaccine candidate based on the Hexapro variant and developed by Sanofi Pasteur failed to elicit nAbs in mice and non-human primates 97 .…”
Section: Discussionsupporting
confidence: 74%
“…S813 S and T813 S was separately expressed firstly (Figs 6A). In our study, SARS2 S contained six proline substitutions to generate stabilized and soluble prefusion form [40][41][42]; SARS S also contained two stabilizing proline mutations in S2 subunit according to an effective stabilization strategy [43,44]. The results showed that S813 S and T813 S proteins had similar affinities towards the ACE2 receptor, indicating that S813T mutation had no effect on S protein receptor binding (Fig 6B).…”
Section: The S813t Mutation Has No Effect On S Protein Interactions W...mentioning
confidence: 87%
“…The role of T cell immunity is another important consideration for optimized S antigens which is suggested to play a role in limiting severe-to-critical COVID-19 [84]. S-6P was shown to induce higher frequencies of antigen-specific CD8 + T cells producing Th1 cytokines than S-2P while trimeric RBD linked to the HR1 and HR2 domain of S2 induced RBD-specific IL-4 and INF-Ψ producing memory T cells [85, 86]. Future studies should aim to examine whether mutations in S2D14 might have introduced new epitopes and assess the impact of T cell immunity on limiting disease severity after immunization with S2D14.…”
Section: Discussionmentioning
confidence: 99%
“…A significant finding in our work is that although vaccination of mice with either S2D14 or S-2P results in the elicitation of similar IgG titers, S2D14 elicits a higher functional response that was more effective than S-2P in neutralizing the ancestral Wuhan strain and variants of concern (Alpha, Beta, and Delta). A recent report of the immunogenicity of recombinant VSV vectored S-6P found that the enhanced stability and expression of S-6P led to elicitation of a more effective nAb response at lower doses than S-2P against the Wuhan strain and VoC including Alpha (B.1.1.7), Gamma (P.1), Beta (B.1.351), Epsilon (B.1.427), and Delta (B.1.617.2) strains [85]. Combined with enhanced expression, vaccination with S2D14 could translate well into dose-sparing effects when delivered in a recombinant setting, but also may translate to a lower dose when delivered by alternative platforms such as mRNA or replication-competent viral vectors.…”
Section: Discussionmentioning
confidence: 99%